The use of gallium-67 in pulmonary disorders - Siemsen, Jan K.; Grebe, Siegfried F.; Waxman, Alan D. (Seminars in nuclear medicine, 1978)
Imaging of the chest cage with gallium-67 ( 67Ga) citrate is relatively easier to perform and interpret than imaging of the abdomen, because normally pulmonary concentration is low after 48 hr and physiologic accumulation in bones and breast can be recognized by its distribution. Modern scintillation detectors, particularly large field cameras with multiple pulse-height analyzers, give substantially better gallium images than those available in the past. Because of the nonspecific affinity of gallium through neoplastic and inflammatory processes, its value in the differential diagnosis of pulmonary diseases is limited. However, based on the literature and our own observations in over 1100 patients with established diagnosis of a variety of pulmonary diseases, we feel that the judicious use of 67Ga in selected patients is helpful in answering specific questions. These include preoperative evaluation of hilar and mediastinal involvement in pulmonary neoplasms, differential diagnosis of pulmonary infarctions and bacterial pneumonias, evaluation of pulmonary infiltrates regarding infectious etiology, follow-up of sarcoidosis on corticosteroid treatment, assessment of inflammatory activity in interstitial fibrosis and, in selected cases, early detection of neoplastic and inflammatory diseases before radiography becomes abnormal, such as diffuse carcinomatosis and Pneumocystis carinii infection. Potential large-scale application of pulmonary gallium imaging could be found in the screening of subjects exposed occupationally to noxious dust and in long-term serial follow-up of pulmonary tuberculoisis patients for treatment response and reactivation. However, it remains to be seen whether gallium imaging statistically provides essential additional information in these indications when compared to cheaper conventional techniques.